2023
DOI: 10.1002/adma.202300813
|View full text |Cite
|
Sign up to set email alerts
|

Nacre‐Mimetic Nanocomposite Aerogels with Exceptional Mechanical Performance for Thermal Superinsulation at Extreme Conditions

Abstract: Thermal protection under extreme conditions requires materials with excellent thermal insulation properties and exceptional mechanical properties to withstand a variety of complex external stresses. Mesoporous silica aerogels are the most widely used insulation materials due to their ultralow thermal conductivity. However, they still suffer from mechanical fragility and structural instability in practical applications. Herein, a nacre‐mimetic nanocomposite aerogel, synthesized via in situ growth of inorganic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…These reductions can be attributed to the poor thermal conductivity of OTM . In this study, the higher the OTM content, the lower the thermal conductivity of the OTM-GO/Al 2 O 3 /PDMS nanocomposites. , …”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…These reductions can be attributed to the poor thermal conductivity of OTM . In this study, the higher the OTM content, the lower the thermal conductivity of the OTM-GO/Al 2 O 3 /PDMS nanocomposites. , …”
Section: Resultsmentioning
confidence: 58%
“…39 In this study, the higher the OTM content, the lower the thermal conductivity of the OTM-GO/Al 2 O 3 /PDMS nanocomposites. 40,41 As shown in Figure 3a the thermal response time of the OTM-GO/Al 2 O 3 /PDMS nanocomposites is positively correlated with their thermal conductivity: the higher the thermal conductivity, the faster the response. 42 Figure 3d depicts the thermal response processes of the different samples.…”
Section: Resultsmentioning
confidence: 95%
“…High porosity and low density of aerogels with nanomicro–multistage porous structure often result in good thermal insulation and thus are widely used as thermal insulation materials , or radiative cooling materials. ,,, It was found that adding acetone reduced the thermal conductivity of the PVA aerogel from 0.0492 to 0.0421 W/mK and reduced the thermal diffusion coefficient from 0.5815 to 0.5490 mm 2 /s (Figure f) resulting from the structural changes which increased the proportion of micro- and nanopores inside the aerogel and reduced the macro-gaps . Further, the incorporation of SiO 2 particles made the thermal conductivity decreased to 0.0390 W/mK and decreased the thermal diffusion coefficient to 0.4770 mm 2 /s.…”
Section: Resultsmentioning
confidence: 99%
“…The BMT-mimetic structures are expected to solve this problem. Recently, Zhang et al 769 prepared a nacre-mimetic nanocomposite aerogel via in situ growth of the inorganic mineral in a lamellar cellulose nanofibrous network. The preparation process involved sol–gel preparation of mesoporous polymethylsilsesquioxane in a layered bacterial cellulose gel network, followed by ambient pressure drying.…”
Section: Applications Of Bmt-inspired Synthetic Materialsmentioning
confidence: 99%